Comprehensive study on critical micellar concentrations of SDS in acetonitrile-water solvents - Šteflová, Jana; Štefl, Martin; Walz, Sarah; Knop, Michael; Trapp, Oliver (Electrophoresis, 2016)
The CMC is one of the fundamental characteristics of surfactants and its determination is crucial for detail understanding of micelles formation. In this study the CMC of SDS in presence of ACN was determined by two independent experimental techniques, capillary electrophoresis and fluorescence correlation spectroscopy (FCS). Yet, studies of SDS micellization in solutions containing ACN as organic modifier are sparse and inconsistent in literature. The measurements were performed for various ACN contents in the range of 0-50% v/v. At ACN contents of up to 10% v/v the CMC is lower when compared to the aqueous solution, while increasing ACN content causes a significant increase of the CMC. Formation of micelles was observed up to ACN concentrations of 35% v/v, which is in contrast to most of the reports in literature. Based on the results of the FCS experiments, we were able to confirm that presence of ACN causes a gradual increase of the size of the micelles with increasing concentration of SDS. Simultaneously, we proved that the classical conductivity approach for the determination of the CMC does not yield reliable results in the presence of higher content of an organic modifier such as ACN.
Gesehen am 07.08.2017